2015
DOI: 10.1108/jap-02-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

“Winning and losing”: vulnerability to mass marketing fraud

Abstract: Purpose -The purpose of this paper is to report the findings from a small qualitative study of victims of mass marketing fraud (MMF), exploring how they become involved in such activity and then sustain their involvement. The article concludes with recommendations for practitioners involved in supporting vulnerable older people.Design/methodology/approach -The paper considers a small exploratory qualitative study into the vulnerability of older people (n=3) to MMF from the perspectives of the 'victims' of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The findings also reveal the significance of psychological and emotional factors in scam engagement (Sprenge et al, 2017). This includes how individuals are groomed into trusting relationships with scammers, and how ultimately the discovery of a scam undermines selfconfidence and trust in others (Olivier et al, 2015). The findings illustrate the role of high emotional arousal in the presentation of scams which are designed to elicit emotional responses in the victims, for example offering a time limited opportunity of a lifetime (Fischer, Lea and Evans, 2013).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The findings also reveal the significance of psychological and emotional factors in scam engagement (Sprenge et al, 2017). This includes how individuals are groomed into trusting relationships with scammers, and how ultimately the discovery of a scam undermines selfconfidence and trust in others (Olivier et al, 2015). The findings illustrate the role of high emotional arousal in the presentation of scams which are designed to elicit emotional responses in the victims, for example offering a time limited opportunity of a lifetime (Fischer, Lea and Evans, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…Social isolation however describes a situation in which the individual lacks social connections or contacts. Feeling lonely or having no social contacts may increase emotional vulnerability and as a result increase susceptibility to responding to a scam (Reibolt and Vogel, 2003;Olivier et al 2015).…”
Section: Loneliness and Social Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to socio-demographic characteristics, such as age and education of fraud victims, in general, the literature is fairly sketchy, with much of the research focussing on the elderly given that it is presumed they are more at risk (ACCC, 2016;Bolimos and Choo, 2017;James, et al, 2014;Oliver, et al, 2015;ONS, 2016c;Titus and Gover, 2001). Those who report cyber-frauds tend to be older (ACCC, 2016) and there is a view that those who are uneducated are more likely to be scammed (Titus and Gover, 2001), although empirical research is needed to support this belief.…”
Section: Victims' Socio-demographic Profilementioning
confidence: 99%
“…There have been mixed findings on age differences and vulnerability to scams. Some suggest that older adults are more vulnerable to MMF, 16 , 17 while others have found that older individuals are victimized to a similar extent to those in their midlife, 18 those in their midlife are more likely to become victims compared to older and younger people. 1 , 2 With regards to romance scams, it is often reported by authorities that victims are more likely to be middle aged.…”
Section: Current Studymentioning
confidence: 99%